120. Safety, Reactogenicity, and Immunogenicity of Three Different Doses of VAC52416 (ExPEC10V) in Adults Aged 60–85 Years in a Randomized, Multicenter, Interventional, First-In-Human, Phase 1/2a Study. (15th December 2022) - Doua, Joachim; Fierro, Carlos; Sarnecki, Michal; Spiessens, Bart; Go, Oscar; Davies, Todd; van den Dobbelsteen, Germie; Poolman, Jan; Haazen, Wouter
Abstract: Background: This Phase 1/2a study (NCT03819049) assessed the safety, reactogenicity, and immunogenicity of 3 doses of VAC52416 (ExPEC10V), a vaccine candidate to prevent invasive extraintestinal pathogenic Escherichia coli (ExPEC) disease. Methods: Data from Cohort 1 are described. The observer-blind, active-controlled design included a 28-day screening, vaccination (Day 1), and 181-day follow-up. Participants (60–85 y) were randomized to a single dose of 1 of 5 vaccines (0.5 mL, intramuscular): ExPEC10V-high (n=104), -medium (n=102), or -low (n=104) dose; ExPEC4V (n=52); or pneumococcal 13-valent (PCV13; n=54) (Table 1 ). Solicited local and systemic adverse events (AEs) until Day 15, unsolicited AEs until Day 30, and serious AEs (SAEs) until Day 181 were assessed. Immunogenicity via electrochemiluminescent (ECL)-based immunoassay and multiplex opsonophagocytic assay (MOPA) was assessed on Day 15. Safety and immunogenicity outcomes were used to select the optimal ExPEC10V dose to be studied in Cohort 2. Table 1. Study Vaccination Dose EPA, a genetically detoxified form of exotoxin A derived from Pseudomonas aeruginosa; PS, polysaccharide. ExPEC4V consisted of the O-antigen PSs of the ExPEC serotypes O1A, O2, O6A, and O25B separately bioconjugated to the EPA carrier protein. ExPEC10V consisted of the O-antigen PSs of the ExPEC serotypes O1A, O2, O4, O6A, O8, O15, O16, O18A, O25B, and O75 separately bioconjugated to the EPA carrier protein. The EPA (µg) was calculated using a ratio of 0.276 for PS/EPA. However, the final EPA dose was confirmed at the release. Results: 416 participants were included (median age, 64.0 years; 54.8% female). Incidence of solicited AEs was higher in the pooled ExPEC10V groups (local, 160 [51.6%]; systemic, 135 [43.5%]) than with ExPEC4V (local, 15 [28.8%]; systemic, 17 [32.7%]) (Table 2 ). The high-dose ExPEC10V group experienced a lower or similar incidence of most solicited AEs relative to the PCV13 group (local, 40 [74.1%]; systemic, 26 [48.1%]). A slightly higher incidence of solicited local AEs was reported with the high ExPEC10V dose, relative to low or medium. Five SAEs, not vaccine-related, were reported. An ECL-based immunoassay revealed a robust total IgG antibody response to ExPEC10V against all vaccine serotypes (geometric mean fold increase: low, 2.33–9.54; medium, 2.38–10.05; high, 3.06–12.31). Opsonophagocytic killing activity was demonstrated against all but one serotype (O8). Table 2. Summary of Solicited Adverse Events *Among randomized patients with a vaccine administration documented from the vaccination until Day 15. AE, adverse event. Data are n (%). Participants are counted only once for any given event, regardless of the number of times they actually experienced the event. No Grade 4 solicited AEs were reported. Conclusion: ExPEC10V is highly immunogenic and well tolerated; no safety issues were identified. High dose ExPEC10V was selected as optimal and will be further characterized in Cohort 2 and long-term follow-up. Because the MOPA lacked sensitivity to detect responses to the O8 serotype, it will be removed from vaccine formulation; ExPEC9V will proceed with clinical development. Disclosures: Joachim Doua, MD, MPH, Janssen: Employee|Janssen: Stocks/Bonds Michal Sarnecki, MD, Janssen: Employee|Janssen: Stocks/Bonds Bart Spiessens, PhD, Janssen: Employee Oscar Go, PhD, Janssen: Employee of Janssen Research & Development LLC. Todd Davies, PhD, Janssen: Employee of Janssen Research & Development Germie van den Dobbelsteen, PhD, Janssen: Employee of Janssen Vaccines & Prevention B.V.|Janssen: Stocks/Bonds Jan Poolman, PhD, Janssen: Janssen Vaccines & Prevention B.V.|Janssen: Stocks/Bonds Wouter Haazen, MD, MSc, Janssen: Employee of Janssen Research & Development.